2010
DOI: 10.1177/0146167210382662
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Social Engagement Among Lonely Individuals: The Role of Acceptance Cues and Promotion Motivations

Abstract: Lonely individuals typically fear negative evaluation and engage in overly cautious social behaviors that perpetuate their social isolation. Recent research has found analogous security-oriented (i.e., prevention-focused) responses following experiences highlighting concerns with social loss but differing growth-oriented (i.e., promotion-focused ) responses, such as attempts at social engagement, following experiences highlighting concerns with social gain. The present studies thus investigated whether fosteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 48 publications
3
32
2
Order By: Relevance
“…Considering the benefits of grit, we might envision interventions that strengthen these mechanisms: in the face of failure, individuals could focus on and foster positive emotional reactions and expectations. Indeed, under conditions of threat, inducing individuals to focus on positives increases engagement in difficult social interactions (Lucas, Knowles, Gardner, Molden, & Jefferis, 2010;Richeson & Trawalter, 2005). These findings where simple primes impact behavior in real-life situations are heartening, as only small modifications may be needed to shift emotions and expectations to thereby increase persistence when people face the fear of failure.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the benefits of grit, we might envision interventions that strengthen these mechanisms: in the face of failure, individuals could focus on and foster positive emotional reactions and expectations. Indeed, under conditions of threat, inducing individuals to focus on positives increases engagement in difficult social interactions (Lucas, Knowles, Gardner, Molden, & Jefferis, 2010;Richeson & Trawalter, 2005). These findings where simple primes impact behavior in real-life situations are heartening, as only small modifications may be needed to shift emotions and expectations to thereby increase persistence when people face the fear of failure.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, two hundred and fifty participants finished gambling game via either pen-paper or PC and it appears that those who feel lonelier generally less likely to take risks, which is in line with our expectations. Basically, loners are more sensitive to fear-evoking cues as well as possible loss (Masi et al, 2013;Hawkley & Cacioppo, 2010;Vohs, Baumeister, & Chin, 2007), which lead them to a prevention focused mind-set (Lucas et al, 2010). For example, they prefer online relationships rather than in real because in order to minimize anxiety or they are less engaged in workplace due to over self-protection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experimental evidences also found that isolation or rejection would result in dysfunction of hippocampus and prefrontal cortex or overreactions of neural system (Will et al, 2016;Silva-Gomez et al, 2003), which reflected a certain adaption of persistent hyper vigilance on isolated individuals. Accordingly, the feeling of loneliness is able to strengthen the perception of fear provoking cues and lead to a preventive focused mind-set (Lucas et al, 2010). As has been noted in regulatory focused theory, individuals would be motivated to do things they "feel right about", hence, those who aim to seek safety and minimize potential loss would probably stay in preventive orientation towards uncertainties (Higgins, 1997).…”
mentioning
confidence: 96%
See 2 more Smart Citations